Gene Therapy Strategy for Alzheimer’s and Parkinson’s Diseases Aimed at Preventing the Formation of Neurotoxic Oligomers in SH-SY5Y Cells - Assou El-Battari (MDPI AG, 2021)
We present here a gene therapy approach aimed at preventing the formation of Ca2+-permeable amyloid pore oligomers that are considered as the most neurotoxic structures in both Alzheimer’s and Parkinson’s diseases. Our study is based on the design of a small peptide inhibitor (AmyP53) that combines the ganglioside recognition properties of the β-amyloid peptide (Aβ, Alzheimer) and α-synuclein (α-syn, Parkinson). As gangliosides mediate the initial binding step of these amyloid proteins to lipid rafts of the brain cell membranes, AmyP53 blocks, at the earliest step, the Ca2+ cascade that leads to neurodegeneration. Using a lentivirus vector, we genetically modified brain cells to express the therapeutic coding sequence of AmyP53 in a secreted form, rendering these cells totally resistant to oligomer formation by either Aβ or α-syn. This protection was specific, as control mCherry-transfected cells remained fully sensitive to these oligomers. AmyP53 was secreted at therapeutic concentrations in the supernatant of cultured cells, so that the therapy was effective for both transfected cells and their neighbors. This study is the first to demonstrate that a unique gene therapy approach aimed at preventing the formation of neurotoxic oligomers by targeting brain gangliosides may be considered for the treatment of two major neurodegenerative disorders, Alzheimer’s and Parkinson’s diseases.